Distúrbios de Ansiedade em Videojogos - Alexandre Fernandes Rocha (2022)
Nowadays there has been an increase in the number of diagnosed anxiety disorders throughout the world, however, this condition has been largely overlooked by the general public, aggravating the difficulties lived by its patients. Due to its rising popularity over the last few years, as well as its unique interactive nature and ability to influence and inform its players, an investigation was made regarding how videogames are able to inform the public about the struggles inherent to living with high anxiety levels. After researching already existing videogames and interactive experiences that tried to incorporate the theme of anxiety into their story and/or gameplay in a variety of ways, the game "Adventures with Anxiety!" was selected to test the effectiveness regarding the transmission of its own intended message, that being that we must learn to control and work with our anxiety, instead of trying to ignore it completely. As such, a questionnaire directed at university students was elaborated with the aim to quantify the game's success, utilizing a Likert scale in order to do so. Although most of the sample agreed the situations represented in the game were generally realtable and representative of what living with anxiety entails, there was a larger number of participants less satisfied with what the game shows as a healthy way to deal with the condition. Taking all the feedback into consideration, a development guide for a hypothetical game with the same pedagogical objective of informing the public about the struggles of living with high anxiety levels was developed. The following general improvements to be implemented were identified: include more and diverse situations, in order to represent different forms of experiencing anxiety; integrate multiple characters with different awareness levels of their own anxiety; incorporate player decisions in a more fleshed out manner in the game's story, as to make the experience more personal and impactful.